Competing for attention: Is the showiest also the best? - Paola Manzini; Marco Mariotti (Queen Mary University of London, School of Economics and Finance, 2015)
There are many situations in which alternatives ranked by quality wish to be chosen and compete for the imperfect attention of a chooser by selecting their own salience. The chooser may be "tricked" into choosing more salient but inferior alternatives. We investigate when competitive forces ensure instead that "the showiest is the best", that is, when the best alternative is maximally salient (and the one that gets picked most often) in equilibrium. We prove that the structure of externalities in the technology of salience is key. Broadly speaking, positive externalities favour correlation between quality and salience.
Keywords: D01; 330; Consideration sets; Bounded rationality; Stochastic choice